Anomali Dalam Pelaksanaan Pelayanan Gereja di Masa Kini - Djone Georges Nicolas (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Christian life is closely related to the world of ministry and the church, because the purpose of church attendance is to serve and enlighten the world. To serve is to be a blessing to those who are served, so that Jesus Christ himself set an example when he was present in the world in human form by serving selflessly and without limits. However, these days there are people who call themselves servants of God or ministers in the church who act in the name of ministry to achieve personal ambitions. This study aims to analyze the causes of anomalies in the implementation of church services today. The results: First, there is a good understanding of the nature and purpose of